Cover Feature: Dynamic Studies on Kinetic H2/D2 Quantum Sieving in a Narrow Pore Metal–Organic Framework Grown on a Sensor Chip (Chem. Eur. J. 46/2019). Issue 46 (27th June 2019) - Paschke, Benjamin; Denysenko, Dmytro; Bredenkötter, Björn; Sastre, German; Wixforth, Achim; Volkmer, Dirk
Abstract : A metal–organic framework (MFU‐4) with ultra‐narrow pores has been integrated on a specially designed sensor, with response in the range of milliseconds, and based on surface acoustic waves (SAWs). Selective diffusion of D2 in H2 /D2 mixtures below 64 K has been observed due to kinetic quantum‐sieving. More information can be found in the Communication by G. Sastre, A. Wixforth, D. Volkmer, et al. onpage 10803 .